The Role of Housewives Groups in Meeting Family Economic Needs through Online Business in Pantai Gemi Village, Stabat District, Langkat Regency - Tiara Azahra; Agus Suriadi (Britain International for Academic Research (BIAR-Publisher), 2024)
This research discusses the role of housewives' groups in meeting family economic needs through online businesses. Generally, meeting the economic needs of the family is the responsibility of every parent in a family, especially fathers and generally those responsible for caring for children and taking care of home and kitchen affairs are mothers. However, along with the times that are currently underway, the role of mothers is no longer just caring for children and taking care of home and kitchen affairs but also plays a role in meeting the economic needs of the family due to several factors, one of which is due to the increasing economic needs of the family and the lack of father's income to meet the economic needs of the family. The changing roles experienced by housewives can trigger new problems for the family, namely the lack of maternal attention to household affairs which is the main responsibility of housewives. So that this makes the emergence of various ideas that can be used as a solution so that housewives can carry out two roles (as mothers and workers) at the same time maximally. One of the jobs that can be done by housewives to be able to increase income and still be able to take care of the house is to become an online trader. Time efficiency is one of the main advantages for online business entrepreneurs. This research uses a qualitative approach with descriptive methods.